Trend Analysis of Rainfall in the Phu Quoc Island - Quang Hung, Nguyen; Xuan Hien, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 4DO - 10.25073/2588-1094/vnuees.4683, 2021)
Assess the trend of rainfall change in Phu Quoc island is an interesting topic which establishes a scientific basis for rainfall forecast trends as well as regional development planning. Rainfall measurement data from 1985 to 2018 was used to analyse with different methods included Sen’s slope, linear regression, Mann-Kendall (MK) test, CV coefficient (Coefficient of Variation), PCI (Precipitation Concentration Index); examine drought level over time by using SPI - standardized rainfall index. Results show that, according to the linear regression analysis, regional annual rainfall is not much fluctuated, the rainy season and annual rainfall tend to decrease, while rainfall in the dry season tends to increase. According to Sen’s slope chart, July rain gains highest increasement, while that of August tends to decrease most. In general, the precipitation concentration index revealed the presence of a high and very high concentration of rainfall.